Authoritarianism on the Front Page: Multimodal Discourse and Argumentation in Times of Multiple Crises in Greece - Groarke, Leo (Informal Logic)

(untitled) (Informal Logic, 2026)
This article reviews Dimitris Serafis’ Authoritarianism on the Front Page: Multimodal discourse and argumentation in times of multiple crises in Greece. (John Benjamins, 2023)